2013
DOI: 10.1016/j.ygyno.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of co-factors in the progression from human papillomavirus infection to cervical cancer

Abstract: Objective Co-factors for cervical cancer, including oral contraceptive (OC) use, smoking and multiparity have been identified; however, the stage at which they act in cervical carcinogenesis is not clear. We compared established risk factors among women with CIN2 and CIN3 to evaluate the heterogeneity of these factors in precancer and also assessed their role during cervical carcinogenesis. Methods The current analysis included 2783 women with various stages of cervical disease who were enrolled in the Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 30 publications
3
87
0
13
Order By: Relevance
“…Prior clinical, epidemiological, and animal model results suggest that estrogen and ERα are critical to CxCa development and maintenance (16,20,21). Consistent with this, 217 of 1,115 genes previously characterized as estrogen-responsive in breast tissue [Dataset S9 (32)] showed strong differential expression across the cervical samples analyzed here.…”
Section: Epithelial Estrogen Receptor α Expression Decreases Throughosupporting
confidence: 85%
See 2 more Smart Citations
“…Prior clinical, epidemiological, and animal model results suggest that estrogen and ERα are critical to CxCa development and maintenance (16,20,21). Consistent with this, 217 of 1,115 genes previously characterized as estrogen-responsive in breast tissue [Dataset S9 (32)] showed strong differential expression across the cervical samples analyzed here.…”
Section: Epithelial Estrogen Receptor α Expression Decreases Throughosupporting
confidence: 85%
“…These and other results indicate that in high-grade cervical lesions and CxCa, estrogen signaling must largely proceed indirectly through activated fibroblasts in the stromal microenvironment. These findings reveal major differences in the possible tumor-promoting effects of estrogen in CxCa and breast cancer, with corresponding clinical implications (16,20,21).…”
Section: Significancementioning
confidence: 85%
See 1 more Smart Citation
“…8 As regards the use of contraceptive pill, it was observed that its use resulted in almost twice the chances of having epithelial cellular changes, similar to the one found in another study, in which the risk of lesions was 2.42 times in the women that used it for more than 10 years. 33 However, other researches did not show a significant association between the oral contraceptive use and the presence of cellular changes. 34 The oral contraceptives alone have no effect on the progression or development of cervical lesions, but they can act in synergy, increasing the susceptibility to develop highdegree lesions in women infected with HPV.…”
Section: Resultsmentioning
confidence: 93%
“…Higher number of sexual partners (more than 4) proved to be the most important risk factor. Another studies confirmed that the risk of HPV infection persistence, the development of CIN lesions, and cervical cancer increase with the number of sexual partners (10). Early onset of sexual activity, i.e.…”
Section: Introductionmentioning
confidence: 79%